2020
DOI: 10.1002/jbm4.10390
|View full text |Cite
|
Sign up to set email alerts
|

Association of Heel Bone Mineral Density With Incident Disability and Mortality in Community‐Dwelling Older Adults

Abstract: Age‐related bone loss is common in older adults. However, the association of low bone mass with incident disability and mortality is not well established. A sample of 738 participants in the Rush Memory and Aging Project (MAP) was evaluated at baseline for bone mineral density (BMD) using quantitative ultrasound at the calcaneus. An annual interview assessed basic activities of daily living (BADL), instrumental activities of daily living (IADL), mobility disability, and history of hip fracture. The association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
2
2
0
Order By: Relevance
“…The observation that fat mass was higher in females confirms findings from Sweden [ 29 ] and the US [ 26 ], although research in Chinese adults found no evidence of sex differences [ 27 ]. Males had higher heel bone mineral density, supporting previous studies of hand [ 30 ] and heel [ 31 ] bone mineral density. Our finding that arterial stiffness was higher in males supports a review which found greater arterial stiffness in males until at least age 60 [ 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…The observation that fat mass was higher in females confirms findings from Sweden [ 29 ] and the US [ 26 ], although research in Chinese adults found no evidence of sex differences [ 27 ]. Males had higher heel bone mineral density, supporting previous studies of hand [ 30 ] and heel [ 31 ] bone mineral density. Our finding that arterial stiffness was higher in males supports a review which found greater arterial stiffness in males until at least age 60 [ 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…The observation that fat mass was higher in females confirms findings from Sweden 42 and the US 39 , although research in Chinese adults found no evidence of sex differences 40 . Males had higher heel bone mineral density, supporting previous studies of hand 43 and heel 44 bone mineral density. Our finding that arterial stiffness was higher in males supports a review which found greater arterial stiffness in males until at least age 60 45 .…”
Section: Discussionsupporting
confidence: 86%
“…Another cross-sectional study has suggested the higher Hcy concentrations were inversely associated with the BMD in femoral neck and lumbar spine regions ( 58 ), which gave the support that different associations between Hcy levels and body regions for our motivation. Our findings declared that elevated Hcy levels had a significant influence on decreased heel BMD through the MR study design, revealing a novel clue for reducing heel BMD loss as heel BMD has been reported to be a vital risk factor for incident disability and mortality ( 59 ). Thus, this finding has great significance for public health.…”
Section: Discussionmentioning
confidence: 66%